A quebra da unidade e o número decimal: um estudo diagnóstico nas primeiras séries do ensino fundamental - Cunha, Micheline Rizcallhah Kanaan da (2002)
The present study aimed to investigate children´s representations related to divisions of the unit . For this purpose, a diagnostic study was undertaken with 48 children from a Public School, divided in to 4 groups with equal numbers of children from the 2nd to 5th grades. The diagnostic instrument included 21 questions composing 39 items, which referred to 3 different contexts: measure, monetary and mathematics. The children´s answers were given in two different representation systems: oral (natural language) and written (symbolic language). The elaboration of the diagnostic instrument as well as the data analysis and the conclusions were theoretically based on Piaget´s theory of Genetic Epistemology, Vygotsky´s Social-Constructivism and the theories of Nunes and Duval concerning representation registers. Analysis of children´s responses pointed to differences between the oral and written representation systems in favor of oral one. Results also suggested an evolution in performance from the 2nd to 5th grade, although improvements were not great, particularly when responses of the children from the 4th and 5th grades were compared. Moreover, the performance of the 5th grade children was lower than expected